1997
DOI: 10.1021/jm970417o
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plasma Protein Binding on in Vivo Activity and Brain Penetration of Glycine/NMDA Receptor Antagonists

Abstract: A major issue in designing drugs as antagonists at the glycine site of the NMDA receptor has been to achieve good in vivo activity. A series of 4-hydroxyquinolone glycine antagonists was found to be active in the DBA/2 mouse anticonvulsant assay, but improvements in in vitro affinity were not mirrored by corresponding increases in anticonvulsant activity. Here we show that binding of the compounds to plasma protein limits their brain penetration. Relative binding to the major plasma protein, albumin, was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
69
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(71 citation statements)
references
References 44 publications
0
69
0
1
Order By: Relevance
“…5) Rowley and co-workers have shown that the binding of L-701,324 to albumin can be effectively inhibited by pre-treatment with warfarin, a drug that resembles L-701,324 in structure and probably competes with L-701,324 for albumin binding. 5) We have recently shown that simultaneous injection of warfarin dose-dependently increases the brain uptake of a positron-emitter labeled L-703,717 ([ 11 C]L-703,717) in mice.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…5) Rowley and co-workers have shown that the binding of L-701,324 to albumin can be effectively inhibited by pre-treatment with warfarin, a drug that resembles L-701,324 in structure and probably competes with L-701,324 for albumin binding. 5) We have recently shown that simultaneous injection of warfarin dose-dependently increases the brain uptake of a positron-emitter labeled L-703,717 ([ 11 C]L-703,717) in mice.…”
mentioning
confidence: 99%
“…5) Rowley and co-workers have shown that the binding of L-701,324 to albumin can be effectively inhibited by pre-treatment with warfarin, a drug that resembles L-701,324 in structure and probably competes with L-701,324 for albumin binding. 5) We have recently shown that simultaneous injection of warfarin dose-dependently increases the brain uptake of a positron-emitter labeled L-703,717 ([ 11 C]L-703,717) in mice. 6) It was further found that, after the increase in brain uptake by warfarin, the glycine site antagonist was more highly localized in the rodent cerebellum than in regions with high-density NMDA glycine receptors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Only a small number of 4-amino-3-alkyl/aryl-1H-quinolin-2-ones 5 have been described so far. They were prepared starting from 4-hydroxy-2-quinolones, 10-12 4-halogeno-2-quinolones, 11, 13-14 2-aminobenzenecarbonitriles, [15][16][17][18][19] and 2-bromobenzonitrile. 20 Compounds 5 have been employed in the synthesis of indolo[3,2-c]quinolin-6-ones and dibenzonaphtyridine-6,11-diones.…”
Section: Discussionmentioning
confidence: 99%
“…21 To date, few 4-aminoquinolin-2-ones have been tested for biological activity. 7-Chloro-3-phenylsubstituted compounds 5 and their N-alkyl and N-acyl derivatives exhibited in vivo anticonvulsant activity in the DBA/2 strain of mouse 18 and in vitro antagonist activity at the glycine site of the N-methyl-D-aspartate receptor. 17 We believe that the most significant contribution of the present work is the synthesis of novel thiazolo [3,4- …”
Section: Discussionmentioning
confidence: 99%